Promoting family functioning through physical activity: a randomized trial to evaluate the “All in the Family” program - Alfred S. Y. Lee; Chris M. Blanchard; Mark R. Beauchamp; Valerie Carson; Sheri Madigan; Shaelyn Strachan; Leigh M. Vanderloo; Evangeline Streight; Sandy Courtnall; Ryan E. Rhodes (Trials)
Abstract Background Effective family functioning, such as communication, family organization, and family cohesion, is essential for family well-being and child development. Promoting family physical activity (PA) through shared activities offers a promising strategy for enhancing family dynamics. Developing a strong parenting PA identity (e.g., seeing oneself as a parent who supports their child’s PA) and a family social identity around PA (e.g., perceiving the family as an active unit) may further strengthen motivation and commitment to engaging in PA. This study aims to evaluate the efficacy of three family PA interventions: (1) PA education alone; (2) PA education + PA parenting self-regulation skills; and (3) PA education + PA parenting self-regulation skills + PA parenting identity. The primary outcome is family cohesion, a key dimension of family functioning. Secondary objectives include examining the effects of these interventions on (1) family-functioning dimensions of flexibility and organization, (2) child PA levels and parent–child co-participation in PA, (3) parental PA support and its potential antecedents (i.e., parental support constructs derived from the Multi-Process Action Control Framework, and parent-perceived family PA social identity), and (4) exploring potential moderating effects of seasonal variation, child and parent characteristics, intervention adherence, and PA type. Methods The three-armed, single-blind randomized controlled trial compares the efficacy of the three interventions over a 6-month period. Families are eligible if they have a child between the ages of 6 and 12 who is not meeting the Canadian 24-Hour Movement Guidelines for Children and Youth. Participants are randomly assigned to one of the three intervention groups. Family functioning, child PA and parent–child co-participation in PA, parental PA support, family PA social identity, and related constructs (e.g., perceived capability and opportunity, behavioral regulation, and habit) are assessed at baseline, 6 weeks, 3 months, and 6 months post-intervention. Recruitment methods include social media, recruitment poster drops, and community-based promotion. Trial registration ClinicalTrials.gov NCT06098716. Registered on October of 2023, updated on August 2024.